Work Engagement dan Eudaimonic Workplace Well-Being pada Guru SMA - Muhammad Fadlan Sadli; Tuti Rahmi (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyse the relationship between work engagement and eudaimonic workplace well-being among secondary school teachers, emphasising the importance of work engagement as a source of psychological well-being based on meaning and self-actualisation within the school environment. The study employs a quantitative approach with a correlational design. The research sample comprised 45 secondary school teachers selected using total sampling. Data were collected using scales measuring work engagement and eudaimonic workplace well-being, and were analysed using Pearson’s Product-Moment correlation test with the aid of SPSS version 26. The results of the analysis indicate a strong and significant positive relationship between work engagement and eudaimonic workplace well-being (r = 0.661; p = 0.000). These findings suggest that teachers with high levels of work engagement tend to have better workplace well-being, particularly in terms of the meaning of work, personal growth, and a sense of making a positive contribution in the workplace. This study makes an empirical contribution by strengthening the evidence that increased work engagement is a key factor in the development of eudaimonic-based teacher well-being, and can serve as a basis for the formulation of policies and human resource management interventions in the field of education.